A study on factors that influence dividend payment in Malaysian listed company / Azminiey Mohd Noor - Mohd Noor, Azminiey (Bachelor Of Business Administration (Hons) Marketing, 2013)
The dividend policy explains the strategy in the organizations about the payments amount which they announce to investors as profit on shares. This paper seeks to identify the determinants that influents the dividend policy decision by the management for selected company for food industry under consumer sector. This study was conducted on Malaysian companies over 9-years period from 2003-2011. The sample was taken from the 9 companies listed on the main board of Bursa Malaysia in consumer sector. Public listed companies are chosen as a sample study because companies listed in KLSE issue shares publicly to all investors where dividend payments will normally be declared by the companies to their shareholders